Pyranocycloartobiloxanthone a suppressed metastasis ovarian cancer cells via s phase cell cycle arrest and apoptosis - Mashitoh Abd Rahman; Najihah Mohd Hashim; Idris Adewale Ahmed (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ovarian cancer is a deadly disease with a poor prognosis, highlighting the urgent need for novel therapeutic alternatives. Pyranocycloartobiloxanthone A (PA), an exceptional xanthone compound has garnered attention due to its diverse medicinal properties. This study aimed to investigate the anticancer properties of PA on metastatic ovarian cancer SKOV-3 cells. Cytotoxicity was evaluated using an MTT assay, while apoptotic mechanisms were determined using AO/PI double staining, annexin V-fluorescein isothiocyanate, multiple cytotoxicity-3, reactive oxygen species (ROS) production, caspases, real-time PCR, western blot, human apoptosis protein profile array and cell cycle analysis. PA inhibited SKOV-3 cell proliferation in a time-dependent manner, with an IC50 of 7.0 ± 0.5 µg/mL and a selectivity index of 13.2 after 72 h of treatment. PA induced apoptosis through the intrinsic apoptotic pathway and arrested the cell cycle at the S phase. PA stimulated ROS production and disrupted the mitochondrial membrane potential, releasing cytochrome c from mitochondria to the cytosol. Additionally, results from human apoptotic protein profile indicated that 21 proteins were upregulated while 22 proteins were downregulated, including Bcl-2, survivin, and HSP70. These findings suggest that PA has the potential as a lead molecule in the development of a chemotherapy drug for ovarian cancer. However, further research is necessary to evaluate the safety and efficacy of PA in preclinical and clinical settings.